(untitled) (Research, Society and Development, 2022)
Objective: To obtain evidence of validity based on the response processes of the multidisciplinary instrument for tracheal decannulation in adults. Method: Three teams of evaluators participated in this research, which were composed of a professional from the areas that work in the tracheal decannulation process – Nursing, Physiotherapy, Speech Therapy and Medicine. There were two stages of the research: the first involved the application of the instrument by the teams to patients, with the same patient for the team and different patients between teams. In the second stage, a brief interview was carried out individually with each evaluator, to verify their perception of the applicability of the instrument. Result: Regarding the degree of relevance of each item presented in the instrument, greater agreement was observed between the responses by team. Regarding writing, the judges evaluated that the items of the instrument are presented in a clear and objective way. All professional evaluators considered the instrument applicable in clinical practice. Conclusion: The multidisciplinary instrument for tracheal decannulation in adults was validated through evidence-based response processes.